Toxicidad y eficacia de un Bioinsumo a base de extracto vegetal de Verbenaceae Essential Oil para el control de ácaros (Oligonychus sp.) del cultivo de aguacate - Muñoz Cachago, Mauro Daniel (2024)
Bioinputs based on plant extracts are interesting proposals for pest control due to their lower environmental impact and support for the management of pest resistance, therefore this work proposes to characterize a bioinput based on commercial Verbenaceae Essential Oil plant extract. through Gas-mass Chromatography and establish the level of control of the product at different concentrations 0, 1, 2 and 3 mL/L, on mites (Oligonychus perseae), identified on avocado leaves at the laboratory level with follow-up in the time at 0, 24, 48 and 72 hours after application by spraying and the effects on the development stages of these tetranychids; eggs, nymphs and adults. The results obtained allowed us to identify that the main component of this commercial extract is thymol with an average content determined in the raw material samples of 24.59%, with which the bioinput is prepared and determined by the same chromatographic method in 3 product samples an average value of 13.2 g/L of thymol. The results of the acaricidal action are: at 1 mL/L, an average death rate of 46% is achieved; at 2 mL/L, 78% and at 3 mL/L, an average death rate of 86% is achieved. At 24 hours after application, it is finally determined that The best treatment is 2 mL/L in the egg, nymph and adult stages, reaching values over 97%, data that verify the acaricidal action of the bioinput based on commercial plant extract Verbenaceae Essential Oil.